(untitled) (American Journal of Islam and Society, 1991)
The Third Seminar on Islamic Economics, held under the sponsorship of the International Institute of Islamic Thought (IIIT) and the Association of Muslim Social Scientists (AMSS), took on an international character with delegates in attendance from as far east as Malaysia, Egypt, and Saudi Arabia in addition to participants from Canada and the United States. This year’s theme for the conference, "Resource Mobilization and Investment in an Islamic Framework;’ evoked considerable interest among both academicians and practitioners of the Islamic economic reform movement. Evidence of this interest was seen in the large number of research papers received on the subject although, regrettably, funding limitations prevented many a scholar from participating in the meetings. The first day’s sessions opened with brief remarks from Sayyid M. Syeed, general secretary of the AMSS, and Zaidi Sattar, program director for the seminar. Their remarks, while highlighting the significant strides made in the past decade in research on Islamic economics, pointed to the substantial financial and logistical constraints that remain in the advancement of future research in the area. IIIT and AMSS were commended for their past role in this endeavor, and hopes were expressed for a more vigorous role in the future. The highlight of the opening session was the thoughtful inaugural address by Taha Jabir al ‘Alwani, President, IIIT, who emphasized the importance of the “human” element in the organization and management of economic resources as “. . . man is both intellect ready for thought, and hands ready for action.” Citing from the Holy Qur’an and the works of Islamic scholars, he stressed that Islamic thought has much to offer in the emancipation of the ummah from the debilitating influence of colonialism. Development of the mind, he argued, is as critical to a society’s growth process as is the development of economic resources ...